2023
DOI: 10.1186/s12913-022-08934-y
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of rural primary health centers for outpatient services - a study based on Rajasthan, India

Abstract: Introduction Outpatient services are crucial for strengthening primary healthcare and reducing out-of-pocket spending, which has been one of the major causes of impoverishment. So it is also critical to comprehend the people’s preferences in accessing primary healthcare facilities, as government primary healthcare facilities in India are underutilized. The current paper explores the factors that construct the individual’s decision to seek outpatient care in primary healthcare facilities in Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Care through OPD service is crucial for developing and strengthening primary healthcare and reducing the out-of-pocket (OOP) expenditure. [ 14 ] The role of PHCs is important as it can address 80% of the health needs of people and thus reduce the OPD care cost. [ 15 ] Therefore, the availability of doctors in PHCs will add a huge value in the health care system and also improve the accessibility to a greater extent.…”
Section: Discussionmentioning
confidence: 99%
“…Care through OPD service is crucial for developing and strengthening primary healthcare and reducing the out-of-pocket (OOP) expenditure. [ 14 ] The role of PHCs is important as it can address 80% of the health needs of people and thus reduce the OPD care cost. [ 15 ] Therefore, the availability of doctors in PHCs will add a huge value in the health care system and also improve the accessibility to a greater extent.…”
Section: Discussionmentioning
confidence: 99%
“…According to the community feedback received in our study, the different essential components of care such as medicines and tests were available in HWCs. Earlier studies have shown that availability of free medicines is important for government facilities to attract enough patients and to meet their treatment needs [ 23 ]. People appreciated that HWCs provided screening and follow-up and not just episodic care.…”
Section: Discussionmentioning
confidence: 99%
“…This represents a significant advancement as primary care delivered by public sector in India has often been criticised for offering selective primary care [ 10 , 24 , 25 ]. An earlier study had reported that people used the government primary facilities mainly for maternal and child care services [ 23 ]. This was because the PHCs and SHCs provided very few services other than those related to maternal and child health [ 23 – 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rural healthcare delivery and utilization form another significant area of study. Srivastava et al (2023) investigate the use of rural primary health centers, focusing on outpatient services in Rajasthan. This research is integral in assessing the effectiveness of primary healthcare infrastructure in rural areas, which is often the first point of contact for the rural populace.…”
Section: Introductionmentioning
confidence: 99%